AdvancED Flash on Devices Mobile Development with Flash Lite and Flash 10 - Janousek, Scott; Elrom, Elad; Joos, Thomas (Apress : Imprint: Apress, 2009)
AdvancED Flash on Devices begins with a discussion of the mobile development landscape-the different players, tools, hardware, platforms, and operating systems. The second part of the book covers Flash Lite and how to take advantage newer features supported in Flash Lite 3.x. Then, the book covers AIR applications for multiple screens and includes topics such as: How to utilize new features of AIR 1.5 and Flash 10 as well as pitfalls to be aware of when building an AIR application for mobile How to include platform and context awareness for better adaptation How to adopt an application on multiple devices using dynamic graphical GUI Creating two full working real life touch screen mobile application The last part of the book covers creating Flex applications running Flash 9 and 10 in mobile device browsers and includes topics such as: How to adopt Flex for multiple mobile device browsers How to create various video players for Flash Lite and Flash 10 and optimize your content. How to take advantage of Flash Media Server Experienced Flash and ActionScript programmers who want to extend their skills to mobile platforms should find this book a great help in developing in this exciting and expanding marketplace.